Synthesis and mechanical characterization of hydroxyapatite-based biomaterials reinforced with nickel-titanium-magnesium alloys for use in cortical bone implants - Refugio-García María E.; Miranda-Hernández José G.; Gallardo-Mendez Marco A.; Vázquez-Huerta Gerardo; Rodríguez-García José A.; Rocha-Rangel Enrique (Science of Sintering)
In this work, biomaterials consisting of bioactive hydroxyapatite-based ceramic and nickel-titanium-magnesium alloys were made. The biomaterials were obtained through powder techniques involving mechanical milling, uniaxial pressing and pressureless sintering. The purpose of the study was to evaluate the effect of alloys on the mechanical properties of hydroxyapatite, the alloy additions were 0, 20, 30, 40, 40, 50 and 60 wt.%. The results were compared with cortical bone samples of bovine origin. From the results, it is possible to comment that, with increasing alloy contents in the hydroxyapatite, the mechanical properties increase considerably. The behavior of the composites reinforced with 50 and 60 wt.% NiTiMg alloy is similar to that of bovine cortical bone. The microstructures of the biomaterials are fine, homogeneous, and similar to those of bovine cortical bone. From the study it can be commented that given the mechanical characteristics of the biomaterials obtained, they could be used as possible bone implants.